Feasibility of Simulation-Based Medical Education in a Low-Income Country: Challenges and Solutions From a 3-year Pilot Program in Uganda. Issue 2 (April 2019) - Bulamba, Fred; Sendagire, Cornelius; Kintu, Andrew; Hewitt-Smith, Adam; Musana, Fred; Lilaonitkul, Maytinee; Ayebale, Emmanuel T.; Law, Tyler; Dubowitz, Gerald; Kituuka, Olivia; Lipnick, Michael S.
Abstract : Summary Statement: Simulation is relatively new in many low-income countries. We describe the challenges encountered, solutions deployed, and the costs incurred while establishing two simulation centers in Uganda. The challenges we experienced included equipment costs, difficulty in procurement, lack of context-appropriate curricula, unreliable power, limited local teaching capacity, and lack of coordination among user groups. Solutions we deployed included improvisation of equipment, customization of low-cost simulation software, creation of context-specific curricula, local administrative support, and creation of a simulation fellowship opportunity for local instructors. Total costs for simulation setups ranged from US 165 to 17, 000. For centers in low-income countries trying to establish simulation programs, our experience suggests that careful selection of context-appropriate equipment and curricula, engagement with local and international collaborators, and early emphasis to increase local teaching capacity are essential. Further studies are needed to identify the most cost-effective levels of technological complexity for simulation in similar resource-constrained settings. Abstract : Supplemental digital content is available in the text.